ANALYSIS OF CHILDHOOD POLIO VACCINE COVERAGE IN THE CENTRAL-WEST REGION UNDER THE INFLUENCE OF THE PANDEMIC AND ANTI-VACCINATION MOVEMENTS (CIPEEX, 2025)
Introduction: Vaccination is one of the most cost-effective and safe interventions, providing both individual protection and collective immunity, and is a mandatory component of health programs. Even so, there has been a decline in adherence rates for key vaccines, including polio. Poliomyelitis, known as polio or infantile paralysis, is a disease that Brazil has not recorded in its wild form for 29 years, but the risk of contracting it still exists due to low vaccination coverage in the country, which has been influenced by the COVID-19 pandemic and the rise of anti-vaccination movements. Objectives: To identify the prevalence of polio vaccination coverage in children, as well as the impact of the pandemic and anti-vaccination movements on polio vaccination coverage.  Methodology: A quantitative retrospective study was conducted through the collection and analysis of data from 2019 to 2021, obtained from the Immunization Program Evaluation System, provided by the Department of Informatics of the Unified Health System (DataSUS). Results: Vaccination coverage in 2021 in the Midwest, the year with the highest mortality rate of the pandemic, showed an overall decrease in polio vaccination rates compared to 2020 and 2019, with 74.22% of the complete schedule, 64.33% of the first booster, and 59.9% of the second booster. Among the federal units, the state of Goiás continued to have the lowest vaccination coverage, with 72.72% of the population fully vaccinated. However, the state of Mato Grosso became the state with the highest total coverage, with 76.29%. Consequently, it was possible to observe reductions in the complete vaccination schedule, first booster, and second booster in 2020 compared to 2019, with reductions of 5.3%, 5.1%, and 1.5%, respectively. Similarly, in relation to 2021, the reductions were 6.6%, 9.3%, and 18.8%, respectively, when compared to 2020. Conclusion: Despite the limitations of the study, as it uses secondary data (DataSUS), a probable causal relationship can be seen between the reduction in polio vaccine coverage and the COVID-19 pandemic and anti-vaccine movements. Therefore, continuous and coordinated commitment from political entities and health professionals is necessary in organizing and planning actions aimed at raising awareness in society about the importance of childhood vaccination against polio.
Keywords: Vaccination Coverage; Polio Vaccine; Anti-Vaccination Movements; COVID-19